2022
DOI: 10.3390/ma15103625
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingival Fibroblast Adhesion and Proliferation on Hydroxyapatite-Coated Zirconia Abutment Surfaces

Abstract: Applying antibacterial coatings to dental implant materials seems reasonable but can have negative influences on desired cell adhesion and healing. In this study, zirconia abutment specimens interacting with gingival tissue were used. The aim was to compare the influence of machined or coated zirconia surfaces on the adhesion and proliferation of human gingival fibroblasts (HGF-1). Surface modifications were performed using atmospheric plasma coating with hydroxyapatite, zinc, and copper. Zirconia specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…More interestingly, the appearance of petal-like nanostructures is similar to the cross-section of tooth enamel after acid etching, i.e., the most highly mineralized tissue in the human body ( Cassari et al, 2023 ; Wu et al, 2023 ). This result suggests that this nanometer topography plays a significant role in regulating the cells’ fate and micro/nanostructure from the biomimetic aspect and could possess excellent biological properties and enhanced stem cell functions ( Wang et al, 2018 ; Bunz et al, 2022 ; Celesti et al, 2022 ). Our results showed that the Cu-TiO 2 group with biomimetic micro/nanostructure was more hydrophilic.…”
Section: Discussionmentioning
confidence: 90%
“…More interestingly, the appearance of petal-like nanostructures is similar to the cross-section of tooth enamel after acid etching, i.e., the most highly mineralized tissue in the human body ( Cassari et al, 2023 ; Wu et al, 2023 ). This result suggests that this nanometer topography plays a significant role in regulating the cells’ fate and micro/nanostructure from the biomimetic aspect and could possess excellent biological properties and enhanced stem cell functions ( Wang et al, 2018 ; Bunz et al, 2022 ; Celesti et al, 2022 ). Our results showed that the Cu-TiO 2 group with biomimetic micro/nanostructure was more hydrophilic.…”
Section: Discussionmentioning
confidence: 90%
“…As an important component of human bone, HA is well known in the field of biomaterial as having good biocompatibility and biological activity [ 1 , 2 , 3 ]. It can produce violent chemical bonds with human bone and promote the growth of new bone.…”
Section: Introductionmentioning
confidence: 99%